Kajian Kuat Tekan Beton Metode Kepadatan Maksimum Dengan Variasi Ukuran Agregat Halus Terhadap Kuat Tekan Beton - Novlia Aneta; H M Shalahuddin; H Gussyafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Concrete as a construction material is very important to continue to develop, increase the strength of concrete is one of the main factors of concrete technology development, toincrease the strength of concrete can be done by several methods. This study aimed to compare the strength of concrete methods SNI with maximum density method with fineaggregate size variations. The conclusion is the compressive strength of the concrete method of maximum density without the 0.075 mm sieve fraction larger, ie 35.02 MPa compressive strength of concrete while the ISO method is 31.16 MPa, the compressive strength of the concrete method of maximum density fractions of 27.11 MPa complete, robust The maximum density of concrete methods without the 0.25 mm sieve fractions of 30.48 MPa, and the method of maximum density without the 0.15 mm sieve fraction that is equal to 34.49 MPa.Keywords: Aggregates, Concrete Compressive Strength